Analysis of Changes in Vegetation Cover Using Satellite Images of Sorok Island in Republic of Korea - Hyungjin Cho; Seungnam Jin; Jong-Seo Won; Youngjun Park (Geo Data, 2025)
This study aims to compare and analyze the past and present vegetation changes on Sorok Island using satellite imagery to understand the current development patterns that damage the island's unique ecological and environmental characteristics. The findings will serve as fundamental data for establishing sustainable management and conservation plans. Sorok Island, located in Goheung-gun, South Korea, has a historical background as a Hansen's disease patient isolation site. Since 1916, limited human intervention has shaped its unique ecosystem. This study uses Sentinel-2 satellite images from 2016 and 2024 to calculate normalized difference vegetation index (NDVI) and analyze vegetation vitality and change rates. Results indicate that NDVI values in 2024 have generally increased compared to 2016, and vegetation vitality has also improved. However, NDVI values for forest areas and inland wetlands have decreased, attributed to forest development and expansion of cultivated land. Future research should include long-term vegetation change analysis and comprehensive studies considering various factors.